HPLC METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ASSAY OF METAMIZOLE, THIAMINE AND PYRIDOXINE IN TABLET - Vevi Maritha (Jurnal Farmasi Indonesia, 2016)
The aim of the present study was develop and validate HPLC method for the simultaneous assay of metamizole, thiamine and pyridoxine in tablet. Metamizole is a substance that is easily hydrolyzed in the presence of water and oxygen. To inhibit the hydrolysis of metamizole during sample preparation prior to HPLC analysis. Sodium sulfite is added and its optimum concentration was investigated. The chromatographic system includes a RP C8(2) column (150x4.6 mm, 5 µm particle size) in conjunction with Photo Diode Array (PDA) detector. The optimal chromatographic condition was obtained using a mobile phase consisting of phosphate buffer 35mM pH 3.0: methanol (80:20), flowrate 1.0 mL/min, and 10 µl injection volume. The metamizole, thiamine and pyridoxine were detected at 275 nm. The hydrolysis of metamizole was successfully inhibited by adding solution containing 1.5 mg/mL sodium sulfite to solvent and 0.5 mg/mL sodium sulfite to mobile phase. The validation results indicate a good specificity and a linear detector responses with r>0.999. The accuracy (% recovery) for metamizole, thiamine and piridoxine were 100.26%; 99.09%; and 100.03%, respectively. The method yields good precision with RSD of metamizole, thiamine and pyridoxine were 2.0912%; 1.4489%; and 0.8418%, respectively. The validated method was successfully applied for simultaneous assay of metamizole, thiamine and pyridoxine in tablet.